Kebijakan Penegakan Hukum Pidana dalam Menanggulangi Perjudian - Ida Arodatul Jannah; Sutopo (Universitas Sunan Drajat Lamongan, Indonesia, 2024)
Criminal law is often used to solve social problems, especially in crime prevention. In particular, the problem of gambling as a form of social disease, a form of social pathology. Enforcement of criminal law to tackle gambling as deviant behavior must continue to be carried out. This is very reasonable because gambling is a threat a real threat to social norms that can lead to individual tensions as well as social tensions. Gambling is a real or potential threat to the nation. Thus gambling can become an obstacle to national development with material-spiritual aspects. Because gambling educates people to make a living in an unreasonable manner and forming a